Mobile Phone Short Message Service (SMS) for Weight Management in Iranian Overweight and Obese Women: A Pilot Study - Somayeh Faghanipour; Eftekharalsadat Hajikazemi; Soghra Nikpour; Shabnam al-Sadat Shariatpanahi; Agha Fatemeh Hosseini (International Journal of Telemedicine and Applications)
We conducted a text message-based intervention for weight management over three months by two months intervention and one month wash-out period. In a quasi-experimental study with control () and experimental group (), 80 overweight and obese employed women were entered. Participants were recruited via announcement. All subjects attended a face-to-face information session and received a booklet that contained food calorie chart and strategies and recommendations for weight management. The experimental group received text messages (SMS) about weight management twice a day for two months, in addition to the information and the booklet which they had received in the information session. Also, the experimental group was instructed to weekly self-weight and to send the data to the principle researcher. All subjects were measured for baseline and secondary weight in a standardized manner by a nurse, and the data were compared between the two groups. Experimental group lost more weight than the control group (1.5 kg difference, ). Text messaging seems to be an effective channel of communication for weight management in Iranian overweight and obese women. The clinical trial registration number is IRCT201204029360N1.